Produktivitas Kerja Berbasis Disiplin Kerja dan Motivasi - Sudarijati, Sudarijati; Palahudin, Palahudin; Rahmawati, Nisa (LPPM Institut Pendidikan Nusantara Global, 2025)
The role of Human Resources is very important to achieve company goals. Therefore, every company is required to increase employee work productivity in order to compete with other similar companies. This study aims to determine and analyze the direct and indirect effects of work discipline on employee work productivity through motivation at PT. Karya Sabar Mandiri. The population in this study were all employees of PT. Karya Sabar Mandiri as many as 52 employees using saturated sampling techniques, which were analyzed using IBM SPSS with the path analysis method. The results of the study showed that work discipline had a direct positive and significant effect on motivation, work discipline had a direct positive and significant effect on work productivity, motivation had a direct positive and significant effect on work productivity, work discipline had an indirect positive and significant effect on work productivity through motivation. Based on these findings, it is recommended that employees can improve their work discipline and motivation in each employee to increase their work productivity.